Hidden Criticism? The Methodology and Plausibility of the Search for a Counter-Imperial Subtext in Paul - Heilig, Christoph (Mohr Siebeck, 2015)
Is there a counter-imperial message beneath the surface of the text in Paul? Christoph Heilig analyzes the letters of the apostle and concludes that the hypothesis that we can identify critical »echoes« of the Roman Empire in Paul's letters needs to be modified for it to be maintained.